Features of the sociocultural identity of a modern student - A. A. Ozerina; O. A. Ulyanina (Russian State Vocational Pedagogical University, 2023)
Introduction. The study of the basic characteristics of the sociocultural identity of a modern student as value and semantic foundations of personal development is relevant due to the cultural and moral transformations of modern society and the practical need to change the system of education in higher education.Aim. The current research aims to reveal the sociocultural characteristics by which a modern student describes himself/herself when compared with a group and to identify groups, communities, which is the subject of identification for the student.Methodology and research methods. The authors used a quantitative approach to the collection and analysis of the data obtained. This made it possible to cover a large sample and obtain statistically reliable results. The theoretical methods of research were historiographical and comparative types of analysis (allowed to formulate the initial provisions of the study); conceptual and terminological analysis of philosophical, psychological, psychological-pedagogical, socio-psychological literature (used to describe the categorical field of the problem); systematisation and conceptualisation of scientific ideas. The following empirical methods were applied: questionnaires, testing. Data processing methods: methods of mathematical statistics (descriptive statistics, Student's T-test, one-factor analysis of variance).Results. The article contains the results of an empirical study of the sociocultural identity of students. The authors defined the foundations of the ideas of modern youth about themselves. In particular, students describe themselves through belonging to family, profession, gender and national groups. The authors identified the groups with which the respondents identify themselves: this is a family and a circle of friends. Moreover, the authors revealed that the socio-cultural identity of students has gender, age differences, and depends on the direction of training at the university. The role of the presented results in the modern international scientific discourse was analysed.Scientific novelty. The authors conceptualised the concept of sociocultural identity and described the mechanisms of its formation; identified the main components in the structure of sociocultural identity of young people; established gender, age and educational differences in the characteristics of sociocultural identity of students; identified dominant groups in the process of identification of a young person with a high degree of significance.Practical significance. The results of the study can be used as a spiritual and moral, value-oriented basis of the education programme in higher education.